(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Sjögren's (SHOW’-grenz) syndrome is a systemic autoimmune, rheumatic disease that affects the entire body. The most common problems are dry mouth, dry eyes, fatigue and musculoskeletal pain in adults. Ten times as many women as men are diagnosed with Sjögren's. While most often diagnosed in women during middle age or after menopause. The congenital heart block (CHB) is defined as the heart block that is diagnosed in fetus (in utero) or within the first 28 days after birth (neonatal period). Congenital heart block is a rare disorder that appears to affect males and females in equal numbers. The most common cause of congenital heart block (CHB) is neonatal lupus due to maternal Sjögren's syndrome, an acquired autoimmune disease caused by transplacental transfer of maternal antibodies to the fetus. Several studies have reported an increased rate of spontaneous abortion and fetal loss associated with Sjögren syndrome. Congenital heart block occurs in a frequency of 1 in 20,000 live births. It has been reported to occur in 2% of Ro-positive mothers [2]; 5% of mothers with a diagnosis of mixed connective tissue and/or Sjögren Syndrome [3] and in 8% of Ro-positive mothers. Here we present an early pre-term neonate that was admitted to neonatal intensive care unit for bradycardia with stable haemodynamics. The mother, who showed no clinical symptoms or any particular history, was transferred to our tertiary centre for profound fetal bradycardia on recent scans. At birth, the infant’s ECG showed a third-degree atrioventricular block and echocardiography was normal. Cardiac neonatal lupus was confirmed with positive maternal anti-Ro antibodies. Under close monitoring, the infant tolerated the bradycardia well (median 72 beats per minute (bpm)) and was discharged on day 21 of life. There was no indication for pacemaker at discharge, but he would be on regular follow-up with a paediatric cardiologist.